Pendidikan Kesehatan dalam Pencegahan Malnutrisi - Apreliasari, Helmy; Risnawati, Risnawati; Wahyuni, Iin (Universitas Aufa Royhan Di Kota Padangsidipuan, 2023)
Adequate nutrition is essential for healthy growth and development during childhood. Malnutrition refers to a pathological state resulting from a relative or absolute deficiency or excess of one or more essential nutrients. Wasting, stunting and underweight are anthropometric indicators commonly used to measure malnutrition in the toddler population. According to the World Health Organization (WHO), wasting, stunting, and underweight are defined as a Z-score of less than 2 standard deviations of weight for height, height for age, and weight for age, respectively.This community service activity aims to increase knowledge related to nutrition and health in preventing malnutrition in children under five. This health education method is carried out using health education methods for mothers with toddlers. The results obtained increase WUS's knowledge about malnutrition and nutritional fulfillment in an effort to prevent malnutrition in toddlers. It is hoped that this community service can increase mothers' knowledge and overcome the problem of malnutrition in toddlers.